COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN PUSAT PEMBERDAYAAN EKONOMI DAN KREATIVITAS MASYARAKAT DI KOTA BANDUNG - wicaksono100, Ferdyansyah - (Decision, 2021)
This article describes the collaborative implementation of a policy that involves different stakeholders in achieving goals, primarily related to community empowerment through the development of inclusive economic and creativity facilities. Through collaborative governance, it is present as a forum for mutual interaction between policy actors in building commitment and cooperation through their roles so that the positive goals of each party are achieved. In this case, it is emphasized through the “ABCGM” pattern that connects the government, private sector, universities, the media, and the community as a foundation in building synergy so that this pattern provides conditions that describe the respective roles between actors and their authorities and even obstacles between actors in building collaboration. . The research method uses a descriptive qualitative approach through data collection techniques of observation, interviews and documentation. This article concludes that the inter-institutions involved in implementing a policy need to be accompanied by commitment as a continuous process of building trust so that collaborative action is able to accommodate the interests and goals of all parties and is inclusively felt by all parties.